CGIAR at SB62, Daily Brief, Edition 3: June 20 - 21 - Edward-Uwadiale, Gina; Miranda, Daniela; Jeanneau, Louise; Koren, Judith; Mukherji, Aditi (2025)
Welcome to CGIAR’s coverage of the Bonn Climate Conference (SB62). This newsletter series is designed to keep the CGIAR Climate Community of Practice informed throughout the negotiations. In each issue, we will provide concise updates on the negotiation tracks we are closely following, highlighting key developments and CGIAR’s contributions. Our aim is to ensure that the community remains engaged and well-informed as the conference progresses, with a strong emphasis on science-based insights and the relevance of food systems across the negotiations.